x = 4
x = -1
x = 0
Equation at the end of step 1 :
((3 • (x3)) - 32x2) - 12x = 0
Step 2 :
Equation at the end of step 2 :
(3x3 - 32x2) - 12x = 0
Step 3 :
Step 4 :
Pulling out like terms :
4.1 Pull out like factors :
3x3 - 9x2 - 12x = 3x • (x2 - 3x - 4)
Trying to factor by splitting the middle term
4.2 Factoring x2 - 3x - 4
The first term is, x2 its coefficient is 1 .
The middle term is, -3x its coefficient is -3 .
The last term, "the constant", is -4
Step-1 : Multiply the coefficient of the first term by the constant 1 • -4 = -4
Step-2 : Find two factors of -4 whose sum equals the coefficient of the middle term, which is -3 .
-4 + 1 = -3 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -4 and 1
x2 - 4x + 1x - 4
Step-4 : Add up the first 2 terms, pulling out like factors :
x • (x-4)
Add up the last 2 terms, pulling out common factors :
1 • (x-4)
Step-5 : Add up the four terms of step 4 :
(x+1) • (x-4)
Which is the desired factorization